Cytoprotective Properties of Makabuhay (Tinospora crispa) Bark Decoction in Cisplatin-induced Nephrotoxic Mice - Alburo, Mark Paolo B.; Ladisla, John Lorenz; Maravillo, Daniel; Paragas, Lawrence O. (International Journal of Scientific Research in Biological Sciences, 2020)
Renal failure in cancer patients is one common problem in chemotherapy. Patients are frequently treated with nephrotoxic antibiotics like cisplatin. After a single dose of cisplatin, thirty-three percent (30%) of patients develops nephrotoxicity that leads to acute kidney injury. This study investigated the cytoprotective properties of makabuhay bark decoction in cisplatin-induced nephrotoxic mice. The makabuhay was extracted through decoction. Nine adult albino mice were used and divided into three groups. Nephrotoxicity was induced through repeated low dose cisplatin intraperitoneally and makabuhay extracts were administered orally. The treatment lasted for five consecutive days and animals were sacrificed under anesthesia on the 6th day after an overnight fast. Blood was collected for blood urea nitrogen and serum creatinine levels evaluation. Results showed that there is a significant difference in the blood urea nitrogen levels of makabuhay treated mice compared to other groups. However, serum creatinine levels among treatments did not show any significant difference. On the other hand, kidney sections of mice were prepared and interpreted. The normal control group showed normal kidney tissues. Kidney sections from the cisplatin group showed severe renal degeneration and necrosis with congestion. The makabuhay treated mice presented moderate renal congestion and degeneration. The data from this study, proved that makabuhay possess cytoprotective properties in cisplatin-induced nephrotoxicity using established mouse model.